Documentation for high yield debt - Webb, David E.; Euromoney Institutional Investor PLC. (London : Euromoney Books, 2001)
This practical guide will ensure that the reader understands the implication of individual documentary terms and can avoid pitfalls in drafting and reading high yield debt documentation. It is a useful guide for anyone involved in high yield debt issues.
Includes index.
oif 31/08/15
Loan
Keywords: Junk bonds